Dynamic Link Inclusion in Online PDF Journals - Probets, Steve; Brailsford, David F.; Carr, Les; Hall, Wendy (Springer, 1998)
Two complementary de facto standards for the publication of electronic documents are HTML on theWorldWideWeb and Adobe s PDF (Portable Document Format) language for use with Acrobat viewers. Both these formats provide support for hypertext features to be embedded within documents. We present a method, which allows links and other hypertext material to be kept in an abstract form in separate link databases. The links can then be interpreted or compiled at any stage and applied, in the correct format to some specific representation such as HTML or PDF. This approach is of great value in keeping hyperlinks relevant, up-to-date and in a form which is independent of the finally delivered electronic document format. Four models are discussed for allowing publishers to insert links into documents at a late stage. The techniques discussed have been implemented using a combination of Acrobat plug-ins, Web servers and Web browsers.